History and prospects of artificial intelligence (Zien Journal of Social Sciences and Humanities, 2023)
This article explores the history and development of artificial intelligence (AI) from ancient times to the present day. It discusses the opportunities presented by AI and highlights the normative documents related to the development of artificial intelligence in Uzbekistan